Small reverberation chambers for radio frequency emission measurements: a radio astronomy feasibility study - Choeysakul, Chittawan (Curtin University, 2015)
To use a Reverberation Chamber (RC) below the Lowest Usable Frequency, this thesis applies: multiple receiving antennas; multiple EUT positions; and a modified validation procedure. Emission measurements are then possible down to the first cavity resonance. The design is based on theory and simulations, and validated by on a prototype. The longer measurement times, compare to conventional RCs are acceptable where sensitivity is of concern, e.g. in radio astronomy or defence applications.